Evaluasi dan Tatalaksana Hipernatremia - Johan, Michael (PT. Kalbe Farma Tbk., 2021)
Hipernatremia didefinisikan sebagai kondisi kadar natrium plasma lebih dari 145 mmol/L. Penyebab hipernatremia bisa dari kehilangan air atau peningkatan kadar natrium. Kehilangan air dapat berupa kehilangan air saja seperti pada keadaan diabetes insipidus atau kehilangan cairan hipotonik seperti pada kehilangan air dari ginjal, gastrointestinal, ataupun kulit. Peningkatan kadar natrium biasanya akibat pemberian cairan hipertonik yang kurang tepat atau iatrogenik. Diagnosis berdasarkan durasi hipernatremia, identifikasi penyebab kehilangan cairan, penilaian status volume, dan osmolaritas urin. Tatalaksana meliputi koreksi penyebab dan koreksi defisit air.Hypernatremia is defined as a condition with a plasma sodium level of more than 145 mmol/L. The cause of hypernatremia can be from water loss or increased sodium level. Loss of water can be in the form of water loss alone, such as in diabetes insipidus or hypotonic fluid loss such as loss of water from the kidneys, gastrointestinal tract, or skin. Increased sodium level is usually the result of improper administration of hypertonic fluids. Diagnostic approach to hypernatremia is based on the duration of hypernatremia, identification of the cause of fluid loss, assessment of volume status, and urine osmolarity. Treatment includes correction of the underlying cause and correction of free water deficits.Â